Fra visibile e invisibile: il paesaggio nelle fonti cartografico-storiche - Gemignani, Carlo A.; Rossi, Luisa (Scienze del Territorio, 2017)
This work, which summarises the results of prolonged archival research, deals with the role that historical cartography can have in a territorialist perspective. The works carried out by French topographers in Piedmont and Liguria, between the late eighteenth and the early nineteenth century, exemplifies the capabilities of displaying territorial phenomena of these figures and therefore their current ‘value in use’. Heirs of the Enlightenment’s advances in astronomy, mathematics and geometry, from a topographic point of view they are indeed witnesses of the pictorial paradigm of imitation of nature. During the nineteenth century, the growing trend towards standardisation, objectiveness and abstraction, would have defined the almost complete disappearance of landscape from maps.